Consumers' attitudes toward CSR of luxury brands in Russia and China - Kolnobrytska, Krystyna; Olšanová, Květa; Neumannová, Pavla; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
The topic of this paper is connected with the Corporate Social Responsibility (CSR) of luxury brands and its perception by their target customers in Russia and China. We are witnessing an increasing significance of CSR activities in the modern society. It became an outcome of the range of economic, environmental, as well as social obstacles which the world is facing nowadays. It has been accompanied by immense role and impact of companies on local society and environment, as well as on the global one. Thus, the CSR has appeared not due to certain popular trend, which engage businesses from different economic fields, but due to real necessity of our Planet and the societies all over the world. Nowadays, the CSR becomes an important part of luxury brands’ business as well, due to increased requirements of business environment and target customers. That is why, the goal of the paper is the investigation of the Russian and Chinese luxury customers’ attitudes to CSR initiatives addressed by luxury brands. The major findings of the paper are the influences of governmental campaigns and luxury companies’ CSR issues' promotion on purchase intention of luxury buyers; Chinese and Russian luxury customers' positive attitude to CSR and strong preference to buy products from socially responsible luxury companies by Chinese, alongside with about significantly lower intention from Russian customers. It is accompanied by significance of Chinese' cultural background in their attitude toward luxury brands' CSR initiatives, and a half lower importance for Russian.
Vedoucí práce: Květa Olšanová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses